2007
DOI: 10.1089/apc.2007.0095
|View full text |Cite
|
Sign up to set email alerts
|

Testing Practices and Knowledge of HIV Among Prenatal Care Providers in a Low Seroprevalence State

Abstract: As the prevalence of heterosexually transmitted HIV increases among women of childbearing age in the United States, so too does the potential for vertical transmission from mother to child. Early maternal diagnosis and appropriate management are critical to minimizing the risk of perinatal infection. We designed a study to evaluate current prenatal care provider testing practices and knowledge of HIV as it relates to pregnancy in a low seroprevalence state. A written questionnaire was mailed to 642 prenatal ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Women account for an estimated 27% of the 1.1 million cases of HIV/AIDS in the United States [3]. Three quarters of HIV infections among women were acquired through heterosexual contact [3], and more than 80% occur in racial and ethnic minorities (African American or Latina) [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women account for an estimated 27% of the 1.1 million cases of HIV/AIDS in the United States [3]. Three quarters of HIV infections among women were acquired through heterosexual contact [3], and more than 80% occur in racial and ethnic minorities (African American or Latina) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Three quarters of HIV infections among women were acquired through heterosexual contact [3], and more than 80% occur in racial and ethnic minorities (African American or Latina) [4]. Overall, HIV infection is the fifth leading cause of death for all US women ages 25 to 34 years and the third leading cause of death in African-American women in that age group [5].…”
Section: Introductionmentioning
confidence: 99%
“…11 Several local surveys have been published assessing HIV testing practices among prenatal care providers. [12][13][14][15][16] These surveys suggest that prenatal HIV screening has improved over time, and is quite high (Ͼ 90%) in several areas. [12][13][14][15][16] A study of family practice clinicians in Rhode Island and Mississippi found that over 93% of providers would recommend an HIV test to a high-risk patient, yet less than 50% recommend HIV testing to sexually active patients aged 18-50.…”
mentioning
confidence: 99%
“…[12][13][14][15][16] These surveys suggest that prenatal HIV screening has improved over time, and is quite high (Ͼ 90%) in several areas. [12][13][14][15][16] A study of family practice clinicians in Rhode Island and Mississippi found that over 93% of providers would recommend an HIV test to a high-risk patient, yet less than 50% recommend HIV testing to sexually active patients aged 18-50. 17 Additionally, in Rhode Island and Mississippi, only 14% and 2% of the surveyed providers reported offering an HIV test to more than 50% of their patient populations, respectively.…”
mentioning
confidence: 99%
“…This was not the case in a study by Msiri, Tadesse and Muula (2008), in which 37% of the respondents were not comfortable attending to an HIV-positive pregnant woman in labour. 33 A 2007 study by Olges et al 26 showed correct practices amongst HCWs in managing HIVpositive pregnant women coming for their first antenatal consultation. Furthermore, in this study 81% responded correctly by providing PMTCT intervention to HIV-positive pregnant women at their first antenatal consultation.…”
Section: Discussionmentioning
confidence: 99%